Self-care practices and diabetes distress among type 2 diabetic patients in Lebanon amidst a multi-crisis context - Ramona Nasr; Eman Swaidan; Chadia Haddad; Wissam Jreije; Abir Abdel Rahman; Joanne Karam (Discover Public Health)
Abstract Diabetes is a major health and economic concern on a global scale. This study focuses on Type 2 Diabetes Mellitus (T2DM) and investigates the relationship between self-care practices and various sociodemographic and psychological factors, including emotional distress. T2DM is recognized as a priority noncommunicable disease, associated with increased premature death rates. A quantitative research methodology was employed, with data collected through an online survey disseminated via social media. A total of 426 participants diagnosed with T2DM were recruited to assess self-care practices and distress among diabetic patients in Lebanon during a period of multiple crises. The study analyzed the participants’ sociodemographic characteristics, diabetes distress through the validated Diabetes Distress Scale (DDS), self-care activities through the validated Summary of Diabetic Self-Care Activities (SDSCA), and physical activity levels through the validated International Physical Activity Questionnaire (IPAQ). Data analysis was conducted using SPSS 25, including descriptive analysis for categorical variables, and bivariate, Pearson correlation, and linear regression analyses to compare the relationships between variables. The findings showed that regimen-related distress was the most significant among participants. Patients experiencing physician distress were less likely to apply self-care practices. Conversely, those suffering from emotional burdens were more adherent to self-care routines. Results also indicated insufficient self-care engagement across all DD domains, with patients adhering to recommended self-care activities for only 1.5 to 2.7 days per week. Notably, all T2DM patients were on medication, with 69.5% using oral anti-diabetic drugs. Family history of diabetes, education level, and physical activity were positively associated with self-care practices, whereas marital status showed no significant association. This study underscores the critical role of education, family history, and emotional burden in shaping self-care behaviors among diabetic patients. Moreover, given Lebanon’s economic and healthcare challenges, the findings emphasize the urgent need for tailored interventions to address diabetes distress and promote sustainable self-care behaviors. Strategies such as telemedicine, behavioral interventions, and psychosocial support programs are recommended to enhance diabetes management in crisis settings.